ANALISIS LAPORAN KEUANGAN SEBAGAI DASAR UNTUK MENGETAHUI EFISIENSI PENGGUNAAN DANA - Utami, Setyaningsih Sri (Universitas Slamet Riyadi, 2010)
ABSTRACT One of the important information which requires to be provided by company is financial statement information. Through financial statement information can be seen the growth which have happened in a company as well as based on the information later can be compiled by steps any kind of which need improve company performance. Financial statement basically is result from accounting process which can be used as appliance to communicate between finance data or activity a company with interested parties with the corporate activity or data. The interested parties to financial position and also growth a company is: the owner, manager, creditor, bankers, the government and investor. Keywords: financial statement, efficiency, balance, balance report Â